2023
DOI: 10.1039/d2ea00149g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of indoor air quality in university residences using low-cost sensors

Abstract: Exposure to air pollutants can cause serious adverse effects on human health; thus, indoor air quality (IAQ) is an important health and safety concern for occupants. A significant fraction of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…Prior studies demonstrated that the use of ultrasonic humidifiers can result in similarly elevated PM 2.5 concentrations in residences. 32 , 33 Participant 3 was the only participant exposed to a higher work-week averaged PM 2.5 concentration while away from work. This exposure was mostly attributed to soil and might have occurred when Participant 3 completed a mowing task at home.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies demonstrated that the use of ultrasonic humidifiers can result in similarly elevated PM 2.5 concentrations in residences. 32 , 33 Participant 3 was the only participant exposed to a higher work-week averaged PM 2.5 concentration while away from work. This exposure was mostly attributed to soil and might have occurred when Participant 3 completed a mowing task at home.…”
Section: Resultsmentioning
confidence: 99%
“…Their photometric measuring method operates via transmission effects, which results in a wider detectable particle-size range than with the SMPS. There are already a number of studies with the mentioned low-cost sensors [39][40][41][42][43][44], where the comparison to different laboratory measuring devices (Optical Particle Counter, SMPS, etc.) showed that the PM2.5 values are comparable [39,41,43].…”
Section: Measurement Devicesmentioning
confidence: 99%
“…There are already a number of studies with the mentioned low-cost sensors [39][40][41][42][43][44], where the comparison to different laboratory measuring devices (Optical Particle Counter, SMPS, etc.) showed that the PM2.5 values are comparable [39,41,43]. As soon as the range allowed by the manufacturer for the relative humidity is exceeded, the measured values are detected incorrectly [41,44].…”
Section: Measurement Devicesmentioning
confidence: 99%
“…The EC sensors generally operate in amperometry mode, wherein the electrochemical reactions between the target gas and an electrolyte produce a current dependent on the gas concentration [ 8 ]. The NDIR technology, widely applied for CO 2 sensor making [ [9] , [10] , [11] ], is based on the spectroscopic principle in which the gas concentrations are proportional to the amount of infrared (IR) light being absorbed by the gas molecules in the air, measured as the difference between the amount of light radiated by the IR lamp and the amount of IR light received by the detector [ 12 , 13 ]. In the PID sensors, the air samples are ionized by UV light; this ionization process leads to the release of electrons and the creation of positively charged ions that generate an electric current signal output.…”
Section: Introductionmentioning
confidence: 99%